2020
DOI: 10.1111/febs.15313
|View full text |Cite
|
Sign up to set email alerts
|

The Warburg Micro Syndrome‐associated Rab3GAP‐Rab18 module promotes autolysosome maturation through the Vps34 Complex I

Abstract: Warburg micro syndrome (WMS) is a hereditary autosomal neuromuscular disorder in humans caused by mutations in Rab18, Rab3GAP1, or Rab3GAP2 genes. Rab3GAP1/2 forms a heterodimeric complex, which acts as a guanosine nucleotide exchange factor and activates Rab18. Although the genetic causes of WMS are known, it is still unclear whether loss of the Rab3GAP‐Rab18 module affects neuronal or muscle cell physiology or both, and how. In this work, we characterize a Rab3GAP2 mutant Drosophila line to establish a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A recent study suggests the molecular mechanism by which Rab18 could regulate macroautophagy. Takats and coworkers [112] used a Drosophila model system which provided evidence that Vps34 Complex I, which is an important protein complex involved in maturation of autophagosomes to lysosomes, and is an effector of Rab18. In this study, they reported a GTP-dependent interaction between Rab18 and the Atg6 component of the complex.…”
Section: Rab18 and Macroautophagymentioning
confidence: 99%
“…A recent study suggests the molecular mechanism by which Rab18 could regulate macroautophagy. Takats and coworkers [112] used a Drosophila model system which provided evidence that Vps34 Complex I, which is an important protein complex involved in maturation of autophagosomes to lysosomes, and is an effector of Rab18. In this study, they reported a GTP-dependent interaction between Rab18 and the Atg6 component of the complex.…”
Section: Rab18 and Macroautophagymentioning
confidence: 99%
“…Finally, it has been suggested that Rab3GAP2, whose loss of function causes SPG69 [ 13 , 176 ], is involved in autophagy at different levels: autophagosome formation and autophagosome–autolysosome maturation [ 67 , 68 ]. Rab3GAP2 is the noncatalytic subunit of the heterodimeric Rab3GAP complex, which has been proposed to regulate Rab18 activity and autolysosome maturation.…”
Section: Autophagy Defects In Hspmentioning
confidence: 99%
“…Rab3GAP2 is the noncatalytic subunit of the heterodimeric Rab3GAP complex, which has been proposed to regulate Rab18 activity and autolysosome maturation. Indeed, autophagy defects are observed in a Rab3GAP2-deficient Drosophila model [ 68 ]. In contrast, another study has also suggested a role of Rab3GAP in autophagy but earlier in the pathway since it was shown that, in human primary fibroblasts, depletion in Rab3GAP2 led to an impaired lipidation of ATG8 family members necessary for autophagosome formation and the autophagy pathway [ 67 ].…”
Section: Autophagy Defects In Hspmentioning
confidence: 99%
“…Prominent among these is Rab1/Ypt1 (Davis & Ferro‐Novick, 2015; J. Wang et al, 2013; Zoppino, Militello, Slavin, Alvarez, & Colombo, 2010), its GEF; the transport protein particle complex (Stanga et al, 2019), and its GAP TBC1D14 (Lamb, Longatti, & Tooze, 2016; Longatti et al, 2012). Many other Rabs, including Rab2 (Ding et al, 2019), RAB3GAPs (Spang et al, 2014), Rab5 (Zhou et al, 2019), Rab6 (Ayala, Kim, & Neufeld, 2018), Rab7a (Heo et al, 2018; Kuchitsu & Fukuda, 2018; Tan & Tang, 2019), Rab10 (Li et al, 2016), Rab11 (Puri et al, 2018), Rab18 (Feldmann et al, 2017; Nian et al, 2019; Takáts et al, 2020), and Rab33B (Morgan, Cutrona, & Simpson, 2019) have also been shown to participate in different steps and contexts of autophagy (Ao, Zou, & Wu, 2014; Chua, Gan, & Tang, 2011; Lamb et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rab2 (Ding et al, 2019), RAB3GAPs (Spang et al, 2014), Rab5 (Zhou et al, 2019), Rab6 (Ayala, Kim, & Neufeld, 2018), Rab7a (Heo et al, 2018;Kuchitsu & Fukuda, 2018;Tan & Tang, 2019), Rab10 (Li et al, 2016), Rab11 (Puri et al, 2018), Rab18 (Feldmann et al, 2017;Nian et al, 2019;Takáts et al, 2020), and Rab33B (Morgan, Cutrona, & Simpson, 2019) have also been shown to participate in different steps and contexts of autophagy (Ao, Zou, & Wu, 2014;Chua, Gan, & Tang, 2011;.…”
mentioning
confidence: 99%